Rejection of Quadruple Interfering Bands in UWB Antenna by Using Stub Loaded SIRs - Kapoor, Jyotsna (My University, 2014)
In today’s era wireless is fastest growing segment of the communication field. Wireless Local Area Network (WLAN) and Worldwide Interoperability for Microwave Access (WiMAX) technologies are the most rapidly growing areas in the modern wireless communication. This actually provides users the mobility to move around within a broad coverage area and still be connected to the network. In today’s environment, technology demands antennas which can operate on different wireless bands and should have different features like low cost, minimal weight, low profile antennas that are capable of maintaining high performance over a large spectrum of frequencies. In today’s environment, technology demands ultra wideband antennas which can operate at wide range of frequencies at lower power level. But due to large number of narrow bands lying in this ultra wideband, there is interference in the one band due to other. So, there is requirement of efficient and a high performance antenna which operates at UWB but also rejects the interfering bands. In order to have transmission in frequency bands other than that of WLAN, WiMAX etc., it is important to reject these interfering bands at these frequencies bands are used in a wide range worldwide. Hence, there will be more interference in the transmission in these bands as compared to other frequency bands. In this thesis report, different techniques for the removal of interfering bands in the UWB antenna are discussed. The work is done by installing different resonators on UWB antenna. First of all, the theory of wave cancellation is discussed. After this metametrial properties are discussed. A SIR and circular SRR are used to reject 2.4, 3.5, and 5.8GHz frequencies along the feed line of UWB antenna. Results are verified on CST Studio 2010. Quadruple band rejection is done by using SIR, square SRR along feed line and CSRR on patch of antenna. Quadruple bands are 2.4GHz, 3.5GHz, 5.8GHz and 8.4GHz. This structure is also designed and simulated on CST 2010. Lastly a Quadruple band rejection is also done by using stub loaded SIRs along the feed line. Here bands are notched at the frequencies 2.4GHz, 3.5GHz, 5.8GHz and 7.5GHz. These stub loaded SIRs improve VSWR. The wideband rejection antenna is then fabricated and tested using Roger 4350 substrate of thickness .802mm. The antenna is tested using Agilent VNA model no. N5222A. The measured results and simulated results are shown. The comparison between the simulated results and the measured results are also shown. The measured and simulated results obtained are similar to each other with a slight variation.
Master of Engineering-Thesis
Keywords: SIR; SRR; UWB; CSRR